The Influence of Board Diversity on Directors’ Networks and Corporate Risk-Taking: A Systematic Review - Abdul Halim, Mohd Hafiz; Said, Roshima; Jamaludin, Mohd Faizal; Mohd Jamil, Muslimah (Journal of Techno-Social, 2025)
Board diversity is increasingly acknowledged as a cornerstone for enhancing the strategic decision-making capabilities of directors’ networks, particularly in the context of corporate risk-taking. This systematic literature review aims to systematically investigate the influence of board diversity on directors’ networks and corporate risk-taking. The key issue highlighted is the need for an updated and structured review to deepen understanding of how board diversity affects directors’ networks and corporate risk-taking. To achieve this objective, an extensive search was conducted for scholarly articles within prominent databases such as Scopus and Web of Science, focusing on studies published between 2024 and 2025. The study adheres to the PRISMA framework for systematic reviews, which yielded twenty-one (n=21) final primary data articles for analysis. The findings are thematically classified into two themes: (1) directors’ networks influence corporate risk-taking, and (2) board diversity influences directors’ networks and corporate risk-taking. The analysis reveals that board gender diversity (BGD) and board ethnicity diversity (BEG) on board diversity moderate the relationship between directors’ networks and corporate risk-taking, depending on the company’s context, governance architecture, and external institutional pressures. In conclusion, strategically integrating board diversity into the corporate risk-taking framework while leveraging directors’ networks cultivates inclusive and accountable decision-making practices.